THE INFLUENCE OF DIGITAL MARKETING AND DIGITAL PAYMENT ON PURCHASE DECISION OF GEN Z AT MSMEs FLAMBOYAN STREET FOOD MANADO - Lantang, Monika Gabriela; Wangke, Shinta Jeanette Camelia; Tulung, Joy Elly (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
In today's digital era, digitalization is a crucial part of daily life, especially in business. It includes digital marketing and payments, which have become essential for companies to compete and adapt. Both digital marketing and digital payments enhance operational efficiency and create new opportunities for growth and innovation. This is particularly beneficial for MSMEs looking to expand their market reach and meet modern consumer needs. This study aims to find out how digital marketing and digital payments affect the purchasing decisions of Gen Z in Flamboyan Street Food MSMEs in Manado. Data were gathered using a quantitative method, by distributing questionnaires via Google Forms to 100 Gen Z respondents. The study examines the influence of digital marketing strategies and the convenience of digital payments on purchase decisions. The findings indicate that both factors significantly impact purchasing decisions. This highlights the need for businesses to incorporate digital technology in their marketing and transaction processes to attract young consumers. The research suggests that MSMEs should leverage digital marketing and payment tools to boost sales within the Gen Z market.   Keywords: Digital Marketing, Digital Payment, Purchase Decision